2021
DOI: 10.7150/jca.51565
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant KIF23 expression is associated with adverse clinical outcome and promotes cellular malignant behavior through the Wnt/β-catenin signaling pathway in Colorectal Cancer

Abstract: Purpose: The aim of the present study was to reveal the clinicopathological significance and prognostic role of kinesin family member 23 (KIF23) in colorectal cancer (CRC) and characterize its biological function and the underlying mechanisms. Methods: Bioinformatics analysis, immunohistochemistry, Western blot and qRT-PCR were utilized to investigate the expression of KIF23 in CRC tissues. The CCK-8 assay, wound healing assay and Matrigel assay were used to detect cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In our study, we found MKLP1 was upregulated in TNBC and associated with prognosis of TNBC by bioinformatic analysis. Several studies showed MKLP1 plays an oncogenic role in several cancer types [11,45]. Moreover, our results illustrated MKLP1 was upregulated in TNBC cell lines and tissues.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our study, we found MKLP1 was upregulated in TNBC and associated with prognosis of TNBC by bioinformatic analysis. Several studies showed MKLP1 plays an oncogenic role in several cancer types [11,45]. Moreover, our results illustrated MKLP1 was upregulated in TNBC cell lines and tissues.…”
Section: Discussionsupporting
confidence: 63%
“…And aberrant Wnt signaling pathway was associated with tumor proliferation, metastasis, stemness and drug resistance [23,24,51,52]. It was reported MKLP1 could activate Wnt/β-catenin signaling pathway in gastric and colorectal cancer [11,45], and then we explored whether MKLP1 affected Wnt/β-catenin signaling pathway in TNBC. Our results showed the related genes of Wnt/β-catenin signaling pathway, such as βcatenin, CyclinD1 and c-myc, were upregulated due to the MKLP1 overexpression, indicating MKLP1 promotes TNBC progression via activating this pathway.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, we found KIF23 was upregulated in TNBC and associated with prognosis of TNBC by bioinformatic analysis. Several studies showed KIF23 plays an oncogenic role in several cancer types [ 13 , 49 ]. Moreover, our results illustrated KIF23 was upregulated in TNBC cell lines and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…And aberrant Wnt signaling pathway was associated with tumor proliferation, metastasis, stemness and drug resistance [ 25 , 26 , 55 , 56 ]. It was reported KIF23 could activate Wnt/β-catenin signaling pathway in gastric and colorectal cancer [ 13 , 49 ], and then we explored whether KIF23 affected Wnt/β-catenin signaling pathway in TNBC. Our results showed the related genes of Wnt/β-catenin signaling pathway, such as β-catenin, CyclinD1 and c-myc, were upregulated due to the KIF23 overexpression, indicating KIF23 promotes TNBC progression via activating this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…KIF18A and KIF23 are members of the kinesin superfamily of microtubule-associated molecular motors, which are related to chromosome separation, intracellular transport, mitotic spindle formation and cytokinesis. Aberrant expressions of KIF18A and KIF23 were related to metastasis and poor prognosis in colorectal cancer [98,99]. TTK could regulate tumor proliferation and differentiation and predict prognosis in colon cancer [100].…”
Section: Discussionmentioning
confidence: 99%